2014
DOI: 10.4238/2014.august.28.9
|View full text |Cite
|
Sign up to set email alerts
|

Association of the g.19074G>A genetic variant in the osteoprotegerin gene with bone mineral density in Chinese postmenopausal women

Abstract: ABSTRACT. Primary osteoporosis is a common health problem in postmenopausal women. This study aimed to detect the association of the g.19074G>A genetic variant in the osteoprotegerin gene (OPG) with bone mineral density (BMD) and primary osteoporosis. The created restriction site-polymerase chain reaction method was used to investigate the g.19074G>A genetic variant. The BMD of the femoral neck hip, lumbar spine (L 2-4 ), and total hip were assessed by dual-energy X-ray absorptiometry (DEXA) in 856 unrelated C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…[53] Many genetic polymorphisms, such as A163G, T245G, T950C and G1181C, A27450T, and G19074A, have been investigated to be associated with BMD and osteoporosis. [54,55]…”
Section: Discussionmentioning
confidence: 99%
“…[53] Many genetic polymorphisms, such as A163G, T245G, T950C and G1181C, A27450T, and G19074A, have been investigated to be associated with BMD and osteoporosis. [54,55]…”
Section: Discussionmentioning
confidence: 99%
“…There are seven polymorphic sites (i.e., Ilu16Thr, Thr20Ilu, Cys87Tyr, Val104Met, Phe117Leu, Cys87Tyr, Cys65Arg) in exon 2 of the OPG gene (6,10,(15)(16)(17)(18). Four of them were mainly studied in Chinese postmenopausal women and the findings confirmed their associations with BMD (10,(15)(16)(17). Three other sites were indicated to be related to idiopathic hyperphosphatasia phenotypes (severe to mild phenotypes), including deformities and fractures in two girls and one boy in Argentina and Turkey (6).…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, it was indicated that women who were homozygous for Phe117 had higher spine and neck hip BMD in comparison with those who were heterozygous (Phe/Leu) or homozygous (Leu/Leu) for position 117 (21). The same situation was found for women who were homozygous for Cys87 in comparison with those who were heterozygous (Cys/Tyr) or homozygous (Tyr/Tyr) for position 87 (22).…”
Section: Discussionmentioning
confidence: 80%